PHYSIOCHEMICAL EVALUATION AND IN VITRO ANTIOXIDANT ACTIVITY OF FEW WONDER SEEDS - Gupta, Deepshikha; Kaur, Prabhkeen (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: This study was an attempt to compare and investigate the physiochemical nature and antioxidant potential of few wonder seeds namely flaxseed, chia, sesame, pomegranate, dill, kalonji, pumpkin and watermelon seeds. Methods: The oil samples and methanolic extract were obtained by extraction of ground seed samples using soxhlet apparatus with n-hexane and methanol respectively. Oil samples were analysed for various physiochemical parameters like specific gravity, refractive index, iodine value, acid value and saponification values. Methanolic extracts were analysed for their antioxidant potential using different methods like TPC, DPPH, FRAP, Ferric-Ferrozine and Î²-Carotene assay. The fixed oil samples were converted into fatty acid methyl esters (FAMEs) and analysed over gas chromatograph for their composition. Results: Pumpkin seeds showed highest phenolic content and highest DPPH radical scavenging activity. Chia seeds showed highest ferric reducing capacity for FRAP and ferric-ferrozine assay. All seed sample showed higher Î²-carotene bleaching than synthetic antioxidant BHA. Conclusion: These wonder seeds investigated have a high potential to combat stress-related diseases owing to good antioxidant potential and presence of polyunsaturated fatty acids. Keywords: Antioxidant assay, GC, Fixed Oil, FAMEs, DPPH, FRAP, Seeds